Semiotic Signs In Walt Disney’s Selected Movie Posters In 2018 - diana rozelin; chandri febri santi; niaturrahmah (English Language, Linguistics, Literature, And Education Journal, 2019)
This research analyzes the semiotic sign in selected posters of walt Disney in 2018, and the selected posters are Avengers Infinity War, Christoper Robin, Marry Poppins Returns, the Black Panther, The Incredibles 2, The Nut Cracker And The Four Realms. The semiotic sign is a sign that analyzes by semiotic theories. The purpose of the research are to know the classification of sign with Charles sanders pierce semiotic theory, the meaning of sign by roland barthes, then the correlation between visual and verbal sign with Gillian dyer theory. This research uses the qualitative descriptive method as reflected by this thesis which explained descriptively. The writer also uses the comparative method in order to compare the diversities in the posters in conclusion. The classification of signs are including Representment: qualisign, sinsign, and legisign. Object: icon, index, and symbol. Interpretant: dyme, dicent, and argument. The meanings are including denotative, connotative and myth. The writer also found the correlation between visual and verbal sign in those six posters.